ANALYSIS OF FACTORS THAT INFLUENCE INTEREST IN USING ACCOUNTING INFORMATION SYSTEMS ON ONLINE SHOPPING PORTALS - Desi Pudwi Handayani; Elen Puspitasari (Jurnal Ekonomi, 2023)
Technology is progressing very rapidly in today's millennial era. Online shopping portals are widely used for almost all people. In online shopping, the system that can be applied is the Accounting Information System. In using technology today, it is influenced by interest in using the features and facilities offered. This research is quantitative research and the data is primary data, because the data is taken directly by researchers without going through intermediaries. The data used is data from people in the city of Semarang who use online shopping portals aged 17 years and over. The respondents totaled 240 people. This study uses instrument tests in the form of validity and reliability tests, classical assumption tests, including multicollinearity tests, heteroscedasticity tests, and normality tests, as well as significance tests between independent variables either individually or together using the t statistical test and the F statistical test. The conclusion of this study is that perceived convenience, perceived usefulness, perceived trust and attitude have an effect on interest in using online shopping, while perceived risk has no effect.